2020
DOI: 10.1002/admi.202000291
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Work Function Reduction by Polyethylenimine Interlayers: Choice of Solvent and Residual Solvent Removal for Superior Functionality

Abstract: Ultrathin polyethylenimine (PEI) interlayers are frequently used to reduce the work function of electrode materials; however, to exploit the full potential of this material for application in optoelectronic devices, further fundamental understanding is required. Here, it is demonstrated that intermixing of PEI deposited from water solution onto the conductive polymer poly(3,4‐ethylene‐dioxythiophene) (PEDOT):polystyrene sulfonate can be avoided by using anhydrous butanol as solvent. At the same time, this choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Pairing of the ssDNA leads to chemical doping of the selective layer on the gate electrode, affects its electrochemical potential (ΔE G ), and modulates the work function. [45,46] This in turn tunes the operating voltage range of the FET without perturbing the transport properties and stability of the channel material. The coplanar gate electrode structure is therefore crucial to achieve segregated sensing operations without polluting the semiconducting layer to avoid interference which might modify the channel transport properties.…”
Section: Selectivity Of the Ssdna Active Layermentioning
confidence: 99%
“…Pairing of the ssDNA leads to chemical doping of the selective layer on the gate electrode, affects its electrochemical potential (ΔE G ), and modulates the work function. [45,46] This in turn tunes the operating voltage range of the FET without perturbing the transport properties and stability of the channel material. The coplanar gate electrode structure is therefore crucial to achieve segregated sensing operations without polluting the semiconducting layer to avoid interference which might modify the channel transport properties.…”
Section: Selectivity Of the Ssdna Active Layermentioning
confidence: 99%
“…They suggested that dipoles are formed in the solution, which assist in electron injection; but this technology is very sensitive regarding the overall electron injection characteristics, as they are added in the form of a film on the cathode. Koch et al examined the influence of preparation conditions of PEI films to reduce the work function of electrode materials [46]. They obtained a homogenous PEI film on ZnO by annealing in a vacuum, which produced an improved electron injection due to the lowered work function at the interface.…”
Section: Interfacial Adhesion Layermentioning
confidence: 99%
“…Notable differences in V OC have been observed by incorporating a polymer electrolyte interlayer with a significant dipole moment between the active layer and electrodes. For example, the dipolar nature of polymer electrolyte interlayers (PFN, poly­(ethylenimine) (PEI), ethoxylated PEI (PEIE)) induces a significant interfacial electric dipole moment which enhances the built-in potential, reduces the work function of the electron extraction layer, and promotes charge collection at the interface. , Specifically, PEIE has been studied as a modifying interlayer for different transport layers and electrodes, and its benefits to reduce the work function of various electrodes, transparent metal oxides including ZnO, conducting polymers, and graphene have been previously demonstrated …”
Section: Introductionmentioning
confidence: 99%